Navigating Risks and Future Trends in Cloud Computing Network Information Security - Zhang, Peishan (Journal of Computer Science and Software Applications, 2021)
This paper elucidates the potential risks associated with cloud computing network information security, delves into the strategic application of network information security technologies, and forecasts the future development trends in cloud computing network security. The ultimate goal is to ensure the robust protection of network information within the cloud computing environment.